1995
DOI: 10.1007/bf00027063
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate tolerance in maize (Zea mays L.). 2. Selection and characterization of a tolerant somaclone

Abstract: The progeny of 104 regenerated maize plants were screened for tolerance to the safe broad-spectrum herbicide glyphosate during seed germination and early growth . Seven somaclones showed varying degrees of resistance to the application of the herbicide at 1 .2 mM (0.1 kg ad . in 400 1 ha ' of water) . Plants capable of a normal growth following treatment with 2 .4 mM (0 .2 kg ha ') glyphosate at the three leaf stage were selfed, and their progeny analyzed . A family able to tolerate the exposure to glyphosate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 25 publications
1
9
0
1
Order By: Relevance
“…A produtividade, morfologia e constituição das cultivares de soja com a resistência incorporada permaneceu igual às linhagens susceptíveis correspondentes. Linhagens de soja com esse gene tratadas com glyphosate, nas doses comerciais, não apresentaram sintomas de fitotoxicidade ou redução da produtividade e qualidade do produto, viabilizando seu uso comercial (Padgette et aI., 1995;Racchi et aI., 1995;Scott et aI., 1998). Várias outras culturas tem recebido atenção no sentido de introdução desse gene que confere insensibilidade de EPSPs ao glyphosate, incluindo milho, arroz, fumo e tomate.…”
Section: Resistência De Culturas Aos Inibidores De Epspsunclassified
“…A produtividade, morfologia e constituição das cultivares de soja com a resistência incorporada permaneceu igual às linhagens susceptíveis correspondentes. Linhagens de soja com esse gene tratadas com glyphosate, nas doses comerciais, não apresentaram sintomas de fitotoxicidade ou redução da produtividade e qualidade do produto, viabilizando seu uso comercial (Padgette et aI., 1995;Racchi et aI., 1995;Scott et aI., 1998). Várias outras culturas tem recebido atenção no sentido de introdução desse gene que confere insensibilidade de EPSPs ao glyphosate, incluindo milho, arroz, fumo e tomate.…”
Section: Resistência De Culturas Aos Inibidores De Epspsunclassified
“…The finding of this study can however be explained by several reasons including the fact that several varieties of maize, including the variety used for this study have been found to be resistant to the toxic effects of glyphosate, the herbicide used to prepare the treated plots. (Racchi et al, 1995;Sergiev et al, 2006). Racchi et al (1995) had found that several species of maize have physiological processes that make them resistant to glyphosate, while Sergiev et al (2006) had noted that the maize plant is able to protect itself against the toxicity of glyphosate through the use of phenylurea cytokinin 4PU-30.…”
Section: Discussionmentioning
confidence: 99%
“…(Racchi et al, 1995;Sergiev et al, 2006). Racchi et al (1995) had found that several species of maize have physiological processes that make them resistant to glyphosate, while Sergiev et al (2006) had noted that the maize plant is able to protect itself against the toxicity of glyphosate through the use of phenylurea cytokinin 4PU-30. The marked decrease in germination count noted in the experimental plots in which overdose of the herbicides were applied can be explained by the fact that the atrazine and metolachlor, that were used as postemergent herbicides in the plots are known to be particularly toxic in overdose, and therefore have the capacity to adversely affect the germination of the maize (Yazdanpak et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Somaclones that are resistant may have an altered transport ability, modified target enzyme or a detoxification mechanism. This has been the case of glyphosate tolerance in maize, in which a variation in the EPSP and DAHP was detected (Racchi et al, 1995). Herbicides interfering with the photosynthetic electron transport system cannot be used for in-vitra selection unless the callus exhibits photosynthetic activity.…”
Section: Xoryzaementioning
confidence: 99%